159k views
5 votes
Please help me :)) im struggling.

Please help me :)) im struggling.-example-1
User Spenser
by
5.0k points

1 Answer

2 votes

Answer:


= -(1)/(3)

Explanation:

Given:


f(x) = (4x - 6)/(x)

Required:

Average range of change over [-3, 6]

SOLUTION:

Find f(-3) and f(6):

To find f(-3), replace x with -3 in the given function


f(-3) = (4(-3) - 6)/(-3)


f(-3) = (-12 - 6)/(-3)


f(-3) = (-18)/(-3)


f(-3) = 6

To find f(6), replace x with 6 in the given function


f(6) = (4(6) - 6)/(6)


f(6) = (24 - 6)/(6)


f(6) = (18)/(6)


f(6) = 3

Average rate of change =
(f(b) - f(a))/(b - a)

Where,


a = -3, f(a) = 6


b = 6, f(b) = 3

Plug in the values into the formula for average rate of change.


= (3 - 6)/(6 -(-3))


= (-3)/(9)


= (-1)/(3)

Average rate of change
= -(1)/(3)

User Monty Khanna
by
6.1k points